1995
DOI: 10.1007/bf02208989
|View full text |Cite
|
Sign up to set email alerts
|

First-pass metabolism of alcohol

Abstract: To determine whether the first-pass metabolism (FPM) of orally consumed alcohol varies with the time of day, 12 healthy male subjects were tested with both oral and intravenous alcohol (0.3 g/kg), in the morning and evening, always 1 hr after the same standard meal. The results revealed no significant differences in FPM (81.6 +/- 11.6 vs 92.8 +/- 10.6 mg/kg) or in any other index of alcohol absorption and metabolism. Eleven subjects were also tested in the evening after treatment with cimetidine, an H2-antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…We found that patients with RYGB and AH had higher rates of cirrhosis after discharge from hospital when compared with controls. First-pass alcohol metabolism by gastric alcohol dehydrogenase is significantly reduced in patients with RYGB, while faster gastric emptying results in uncontrolled exposure to and absorption of alcohol through the small bowel 34 35. As a result, patients with RYGB who ingest alcohol may have higher peak blood alcohol concentrations compared with patients with normal stomach anatomy, which may be more directly toxic to the liver and accelerate the development of cirrhosis 36.…”
Section: Discussionmentioning
confidence: 99%
“…We found that patients with RYGB and AH had higher rates of cirrhosis after discharge from hospital when compared with controls. First-pass alcohol metabolism by gastric alcohol dehydrogenase is significantly reduced in patients with RYGB, while faster gastric emptying results in uncontrolled exposure to and absorption of alcohol through the small bowel 34 35. As a result, patients with RYGB who ingest alcohol may have higher peak blood alcohol concentrations compared with patients with normal stomach anatomy, which may be more directly toxic to the liver and accelerate the development of cirrhosis 36.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the inconsistencies in the gender difference data, the presence of ADH in the stomach provides the first opportunity for the oxidation of ingested alcohol. Therefore, the presence of food in the stomach should slow gastric emptying and reduce BACs (2,9,10). Meals of greater energy density, of greater volume, and of solid food will slow gastric emptying more than meals of lower density, of lesser volume, and of liquid food (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%